1947
DOI: 10.1021/jo01166a005
|View full text |Cite
|
Sign up to set email alerts
|

REACTIONS AND ANALYSIS OF β-CHLOROETHYL SULFIDE IN WATER1

Abstract: The observations of Peters and Walker (1) and Mohler and Hartnagel (2) that the rate of hydrolysis of ß-chloroethyl sulfide (I) in water was first order, independent of the pH and a number of added anions and cations, led the latter authors to point out that this behavior resembled that of an SNi process proceeding by a solvolytic mechanism in which the rate controlling step was an ionization of the carbon-chlorine bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1947
1947
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The kinetics and mechanisms of such a hydrolysis process for sulfur mustard (HD) and its monochloro derivative (CEES) have been extensively investigated. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] These studies have confirmed that the first step is the rapid equilibrium formation of the sulphonium cation (Fig. 3, b).…”
Section: Stability and Aquationmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The kinetics and mechanisms of such a hydrolysis process for sulfur mustard (HD) and its monochloro derivative (CEES) have been extensively investigated. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] These studies have confirmed that the first step is the rapid equilibrium formation of the sulphonium cation (Fig. 3, b).…”
Section: Stability and Aquationmentioning
confidence: 99%
“…By extrapolation of the rate in aqueous dioxane solutions it has been estimated that the first-order rate constant in water at 25°s hould be about 0.4 min.-1. This is four times that of /3-chloroethyl sulfide, k25 = 0.10 min.-1 [half-life at 25°, seven to eight minutes (2,3,4)], and about twice the value reported for ß-(/3'-chloroethyIthio)ethyl ether (X) by Brookfield and Moelwyn-Hughes (5).…”
mentioning
confidence: 60%
“…In connection with speculation concerning the mechanism of hydrolysis of /3-chloroethyl sulfides (2,3,4), it is of interest to compare this order of reactivity for chloro compound and sulfonium salt with examples known to proceed by Sni and by Sn2 mechanisms.…”
Section: Cl-xiiimentioning
confidence: 99%
“…Reactions (1) and (2) [Is+1 * [C1--[HDko -( k3 ) k1 k (7) in which [HD]o is the initial concentration of mustard. This is the integrated rate equation for a sequence of two, consecutive, unimolecular reactions specifically applied to the mechanism shown in Figure 1.…”
Section: -15mentioning
confidence: 99%